19-2g=7

Simple and best practice solution for 19-2g=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19-2g=7 equation:


Simplifying
19 + -2g = 7

Solving
19 + -2g = 7

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + -2g = 7 + -19

Combine like terms: 19 + -19 = 0
0 + -2g = 7 + -19
-2g = 7 + -19

Combine like terms: 7 + -19 = -12
-2g = -12

Divide each side by '-2'.
g = 6

Simplifying
g = 6

See similar equations:

| 4n^2-7=27n | | (16e^4)1/2 | | (1.4x^3+4.4x^2-3.3x)+(-3.1x^3-4.6x^2+73)= | | 2y/7-7/8=5/56 | | -5m+4=6-10m | | 3a^2-26a+30=-5 | | 3z+[-3]= | | 6x-123=-3x+102 | | 8=3w+16 | | 2/3=x/40 | | 24y=8-16y | | 3x(3x^2+3-10x)=0 | | 6n-10=26 | | h=21.5+13.5 | | (x^2-10)=(5x+4) | | [2x+3]=-13 | | n+5=n | | (6x^2-2x+11)+(2x^2+5x-47)= | | w+8.2+.4w=-8.6 | | 3(x+2)-x=5(2x-2) | | 15v-9v=18 | | 2(9x-1)=99-7(3+4x) | | 6v^2-43v+48=6 | | f(x+9)=5x-6 | | 30-8x=4 | | 3x+bx=zforx | | 2sin^2x-11x=5 | | 62=8b+11 | | 3x+27.93=3.99 | | F(x)=2x^3-x^2-ax+10 | | f(x)=5x+9-6 | | -2x-1+5x+9= |

Equations solver categories